Gender, emotions, and tournament performance in the laboratory - Brianna Halladay (Games, 2017)
Individuals face competitive environments daily, and it is important to understand how emotions affect behavior in these environments and resulting economic consequences. Using a two-stage laboratory experiment, I analyze the role of reported emotions in tournament performance and assess how the behavioral response differs across genders. The first stage serves to induce emotions, while the second stage presents the subject with a one-on-one winner-take-all tournament with the individual who generated the feeling, using a real-effort task. Ultimately, I show that women respond to the negative feelings more strongly than men. I find that women increase performance when experiencing negative emotions, while male performance remains unaffected. Remarkably, there is no gender gap in tournament performance when there are negative emotions
Keywords: C16; J16; J22; 330; gender; competition; experimental economics; emotions